Effect of Ruiyun procedure for hemorrhoids (RPH-4) for treating mixed hemorrhoids - Yao Qixian; Wang jinglin; Di Yan; Tang Lingjiao; An Xiaohai; He yu; Xu Jun (结直肠肛门外科)
[Objectives] To investigate the effect of Ruiyun procedure for hemorrhoids (RPH-4) for treating mixed hemorrhoids. [Methods] Sixty-two patients with mixed hemorrhoids treated at the People’s Hospital of Suzhou New District between December 2018 and January 2020 were randomly assigned to the treatment group (n=31) and the control group (n=31). Patients in the treatment group received Ruiyun procedure for hemorrhoids (RPH-4), and those in the control group received Procedure for prolapse and hemorrhoids (PPH). Clinical effectiveness, operation time, intraoperative blood loss, length of hospital stay, wound healing time, and postoperative complications were compared between the two groups. [Results] There was no significant difference in the effective rate between the two groups. Operation time, amount of intraoperative blood loss, length of hospital stay and wound healing time was significantly less or shorter in the treatment group than in the control group (P < 0.05). There was no significant difference in the incidence of complications such as anal distension, anal stenosis, postoperative anal bleeding, anal edema, and urinary retention between the two groups (P > 0.05). The total incidence of postoperative complications in the treatment group was lower than in the control group (P < 0.05). [Conclusion] Ruiyun procedure for hemorrhoids (RPH-4) is equally effective as PPH for treating mixed hemorrhoids. However, Ruiyun procedure for hemorrhoids (RPH-4) is associated with shorter operation time, length of hospital stay, wound healing time, lesser intraoperative blood loss, and lower overall risk of postoperative complications. It has good clinical application value.